Asuhan Keperawatan Jiwa Pada Pasien Gangguan Persepsi Sensori : Halusinasi Penglihatan dan Pendengaran Dengan Pemberian Intervensi Terapi Musik Dangdut di Yayasan Rehabilitasi Mental Griya Bhakti Medika - Rita Donna Marlina; Ayu Pratiwi; Mentari Mentari (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Background: Mental disorders are conditions in which mental functions, thought processes, emotions, feelings, psychomotor and verbal behavior are disrupted which becomes a group of clinical symptoms accompanied by suffering and results in disruption of an individual's humanistic function (Ramadani et al, 2020). One type of mental disorder is schizophrenia, where the main perception disorder in schizophrenic patients is hallucinations. Hallucinations are changes or perceptions that there is unfavorable stimulation from within the individual or from outside the individual accompanied by a reduced, excessive or distorted response (Rustika, 2020). One non-pharmacological implementation strategy for patients with hallucinations is by providing music therapy (Alfionita, 2016). Method: Giving therapy to listen to dangdut music to patients for 4 days is carried out 1 day once therapy for 10-15 minutes. Results: After the intervention of giving menmusic therapy for 4 days, it was found that the patient experienced a decrease in signs and symptoms of hallucinations from initially a score of 8 to 2. Conclusion: Providing dangdut music therapy can help reduce the frequency of hallucinations. This is due to the diversion of the patient's attention from the hallucinatory sounds to the dangdut music he hears. rebuking and music to reduce the symptoms of the hallucinations he was suffering from.